Factors associated with parenting stress among mothers with down syndrome children in Kota Bharu, Kelantan - Ling, Lee Wai (Pusat Pengajian Sains Kesihatan, 2014)
Through research about predictors of parenting stress among mothers of Down syndrome children, hopefully that some information obtained could be utilized to advocate for mental health services for mothers of young children with intellectual disabilities in Malaysia. Depression, anxiety, parenting stress and others negative impacts were observed among the parents of children with Down syndrome. The aim of this study was to determine the parenting stress level and factors that may associate with parenting stress level among mothers with Down syndrome children in Kota Bharu, Kelantan. After obtaining ethical approval from both hospital and USM ethics committees, a cross sectional study was carried out among mothers with Down syndrome children from Pediatrics Clinic Hospital USM and Lion Club’s Down syndrome Center in Kota Bharu. Purposive sampling method was used to recruit the sample. There were 30 mothers being involved in this study. Data were collected using a self- administered questionnaire developed by the researcher according to previous literature. The questionnaire was available in two languages (English and Malays) in which included demographic data, parental stress scale, pediatric symptoms checklist, DASS and COPE. Then, data was being analyzed using the Statistical Package Social Science (SPSS) software version 20.0. Descriptive statistics were used to present the demographic data. The results suggested that the parenting stress level could be significantly associated with child behavioral problems, maternal depression and stress as well as maternal coping methods. By using the cut- off point of 28 from Child Behavior Checklist for children aged more than 6 years old and cut- off of 24 for younger children, 12 (40.0%) of the Down syndrome children had reported having behavioral problems. The mean stress score for mothers with a child having behavioral problems (50.5) was higher than that of those who did not report having behavioral problems (37.1), with a p value less than 0.001. The mean parenting stress score of normal, mild and moderate depression score were 39.9, 50.8 and 51.0, with p value 0.023. The mean stress score of mothers that scored normal, mild as well as moderate stress score were 39.6, 51.4 and 53.5, giving a significant p value of 0.006. The mean COPE score in the study was 79.3 (SD = 9.2), ranging from 66 to 96. The correlation coefficient between mean parenting stress and COPE score was -0.634, with p value <0.001.The parenting stress level among mothers with Down syndrome children was caused by child behavioral problem, then affected by maternal depression and anxiety and lastly buffered by maternal coping methods. Thus, more research should be conducted in order to clarify more about the possible causes of parenting stress level and intervention to alleviate the stress.